2006
DOI: 10.1007/s10902-006-9029-y
|View full text |Cite
|
Sign up to set email alerts
|

The role of social axioms in predicting life satisfaction: a longitudinal study in Hong Kong

Abstract: Hong Kong Chinese, life satisfaction, social axioms, self- esteem.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 34 publications
4
63
0
Order By: Relevance
“…The negative effect of social cynicism on life satisfaction is consistent with results in previous studies (e.g. Lai et al, 2007). The negativity and mistrust of socially cynical individuals hinders their interactions with others and yet may act as a negative interpersonal influence, preventing individuals from creating or maintaining positive relationships with others.…”
Section: Pathways Of Social Cynicismsupporting
confidence: 91%
See 2 more Smart Citations
“…The negative effect of social cynicism on life satisfaction is consistent with results in previous studies (e.g. Lai et al, 2007). The negativity and mistrust of socially cynical individuals hinders their interactions with others and yet may act as a negative interpersonal influence, preventing individuals from creating or maintaining positive relationships with others.…”
Section: Pathways Of Social Cynicismsupporting
confidence: 91%
“…and Hong Kong Chinese (e.g. Lai et al, 2007), but did not reveal the underlying mechanisms. Again, the present research extended this effect to children and adolescents and further identified the mediating variables to explain the predictive framework.…”
Section: Pathways Of Reward For Applicationmentioning
confidence: 82%
See 1 more Smart Citation
“…Furthermore, self-esteem shapes one’s attitudes towards and quality of life. In addition, research suggests that self-esteem mediates the effect of personality traits on one’s life satisfaction (Lai, Bond, & Hui, 2007). In this article, we propose that grit predicts one’s life satisfaction and that self-esteem mediates this relationship.…”
Section: Introductionmentioning
confidence: 99%
“…The present study intends to undertake a qualitative comparison of peak-experiences between Hong Kong and Brazil, where research on subjective well-being has received increasing attention, but mostly focused on peoples' cognitive and affective evaluation of life and factors contributing to happiness concurrently and prospectively (e.g., Ho et al 2008;Kwan et al 1997;Lai et al 2007). In this study, therefore, we adopt a retrospective design, asking Chinese and Brazilians to recollect an early peak-experience, and then coding their narratives to identify commonalities and variations between the two cultures.…”
mentioning
confidence: 99%